A slowly progressive form of limb‐girdle muscular dystrophy type 2C associated with founder mutation in the SGCG gene in Puerto Rican Hispanics. Issue 2 (8th January 2015) - Al‐Zaidy, Samiah A.; Malik, Vinod; Kneile, Kelley; Rosales, Xiomara Q.; Gomez, Ana Maria; Lewis, Sarah; Hashimoto, Sayaka; Gastier‐Foster, Julie; Kang, Peter; Darras, Basil; Kunkel, Louis; Carlo, Jose; et al.
<x xml:space="preserve">Abstract</x> In this report, we describe four unrelated LGMD2C patients of Hispanic descent from the island of Puerto Rico that share a E263K (G787A) mutation within exon 8 of the SGCG gene. A slowly progressive phenotype with prolonged preservation of ambulation is illustrated in two of our patients. We also confirmed the founder effect of this mutation among Puerto Rican Hispanics using linkage analysis and determined that this mutation in affected individuals segregates with alleles inherited from each parent. <boxed-text content-type="graphic" id="mgg3125-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>